Sex-specific differences in SLE - Significance in the experimental setting of inflammation and kidney damage in MRL-Faslpr mice - Saurin, Sabrina; Meineck, Myriam; Claßen, Paul; Boedecker-Lips, Simone Cosima; Pautz, Andrea; Weinmann-Menke, Julia (Autoimmunity (Chur, Switzerland), 2024)
Animal models are an important tool in the research of chronic autoimmune diseases, like systemic lupus erythematosus (SLE). MRL-Faslpr mice are one of different lupus models that develop spontaneously an SLE-like disease with autoantibodies and immune complex deposition that leads into damage of different organs. In contrast to human SLE, both sexes of MRL-Faslpr mice develop a similar autoimmune disease. Due to the sex bias in human and the delayed disease progression in male MRL-Faslpr mice, the majority of studies have been performed in female mice. To determine the suitability of male MRL-Faslpr mice for SLE research, especially with regard to the 3 R-principle and animal welfare, analyses of phenotype, inflammation and damage with focus on kidney and spleen were performed in mice of both sexes. Female mice developed lymphadenopathy and skin lesions earlier as males. At an age of 3.5 month, more immune cells infiltrated kidney and spleen in females compared to males. At the age of 5 months, however, substantially less sex-specific differences were detected. Since other studies have shown differences between both sexes on other manifestations like autoimmune pancreatitis and Sjögren syndrome in MRL-Faslpr mice, the use of male mice as part of 3 R-principle and animal welfare must be carefully considered.Animal models are an important tool in the research of chronic autoimmune diseases, like systemic lupus erythematosus (SLE). MRL-Faslpr mice are one of different lupus models that develop spontaneously an SLE-like disease with autoantibodies and immune complex deposition that leads into damage of different organs. In contrast to human SLE, both sexes of MRL-Faslpr mice develop a similar autoimmune disease. Due to the sex bias in human and the delayed disease progression in male MRL-Faslpr mice, the majority of studies have been performed in female mice. To determine the suitability of male MRL-Faslpr mice for SLE research, especially with regard to the 3 R-principle and animal welfare, analyses of phenotype, inflammation and damage with focus on kidney and spleen were performed in mice of both sexes. Female mice developed lymphadenopathy and skin lesions earlier as males. At an age of 3.5 month, more immune cells infiltrated kidney and spleen in females compared to males. At the age of 5 months, however, substantially less sex-specific differences were detected. Since other studies have shown differences between both sexes on other manifestations like autoimmune pancreatitis and Sjögren syndrome in MRL-Faslpr mice, the use of male mice as part of 3 R-principle and animal welfare must be carefully considered.